Epigenetic Influence of Dam Methylation on Gene Expression and Attachment in Uropathogenic Escherichia coli - Stephenson, Stacy Ann-Marie; Brown, Paul D. (Frontiers in Public Health, 2016)
Urinary tract infections (UTI) are among the most frequently encountered infections in clinical practice globally. Predominantly a burden among female adults and infants, UTIs primarily caused by uropathogenic Escherichia coli (UPEC) results in high morbidity and fiscal health strains. During pathogenesis, colonization of the urinary tract via fimbrial adhesion to mucosal cells is the most critical point in infection and has been linked to DNA methylation. Furthermore, with continuous exposure to antibiotics as the standard therapeutic strategy, UPEC has evolved to become highly adaptable in circumventing the effect of antimicrobial agents and host defenses. Hence, the need for alternative treatment strategies arises. Since differential DNA methylation is observed as a critical precursor to virulence in various pathogenic bacteria, this body of work sought to assess the influence of the DNA adenine methylase (dam) gene on gene expression and cellular adhesion in UPEC and its potential as a therapeutic target. To monitor the influence of dam on attachment and FQ resistance, selected UPEC dam mutants created via one-step allelic exchange were transformed with cloned qnrA and dam complement plasmid for comparative analysis of growth rate, antimicrobial susceptibility, biofilm formation, gene expression, and mammalian cell attachment. The absence of DNA methylation among dam mutants was apparent. Varying deficiencies in cell growth, antimicrobial resistance and biofilm formation, alongside low-level increases in gene expression (recA and papI), and adherence to HEK-293 and HTB-9 mammalian cells were also detected as a factor of SOS induction to result in increased mutability. Phenotypic characteristics of parental strains were restored in dam complement strains. Dam’s vital role in DNA methylation and gene expression in local UPEC isolates was confirmed. Similarly to dam-deficient Enterohemorrhagic E. coli (EHEC), these findings suggest unsuccessful therapeutic use of Dam inhibitors against UPEC or dam-deficient UPEC strains as attenuated live vaccines. However, further investigations are necessary to determine the post-transcriptional influence of dam on the regulatory network of virulence genes central to pathogenesis.